Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1093/cercor/bht324
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Effective Hippocampal–Neocortical Connectivity During Construction and Elaboration of Autobiographical Memory Retrieval

Abstract: Autobiographical memory (AM) provides the opportunity to study interactions among brain areas that support the search for a specific episodic memory (construction), and the later experience of mentally reliving it (elaboration). While the hippocampus supports both construction and elaboration, it is unclear how hippocampal-neocortical connectivity differs between these stages, and how this connectivity involves the anterior and posterior segments of the hippocampus, as these have been considered to support the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
130
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(153 citation statements)
references
References 49 publications
21
130
1
1
Order By: Relevance
“…The anterior memory network, which includes the anterior MTLs and frontal regions, is involved in retrieving general constructs and concepts, and the posterior memory network, which includes posterior MTLs and posterior cortical regions, is involved in retrieving perceptual details (Poppenk et al, 2013;Evensmoen et al, 2015). In support of this view, connectivity between the anterior hippocampus and prefrontal cortex was found to be more involved when constructing or accessing personal memories whereas connectivity between the posterior hippocampus and posterior cortical regions, namely the visual cortex, was more involved when elaborating on the details of those memories once they were retrieved (McCormick, St-Laurent, Ty, Valiante, & McAndrews, 2015).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The anterior memory network, which includes the anterior MTLs and frontal regions, is involved in retrieving general constructs and concepts, and the posterior memory network, which includes posterior MTLs and posterior cortical regions, is involved in retrieving perceptual details (Poppenk et al, 2013;Evensmoen et al, 2015). In support of this view, connectivity between the anterior hippocampus and prefrontal cortex was found to be more involved when constructing or accessing personal memories whereas connectivity between the posterior hippocampus and posterior cortical regions, namely the visual cortex, was more involved when elaborating on the details of those memories once they were retrieved (McCormick, St-Laurent, Ty, Valiante, & McAndrews, 2015).…”
Section: Introductionmentioning
confidence: 87%
“…In thinking about this difference, the results of a recent study by McCormick et al (2015) may be instructive. They found that during the initial, constructive phase of autobiographical event recall, activation was more prominent in the anterior hippocampus and its connectivity pattern resembled that reported in this study.…”
Section: Task Specific Hippocampal Connectivitymentioning
confidence: 99%
“…Examining all nodes in the DMN, which shows strong overlap with the recollection network, we found that connectivity between the hippocampus and posterior neo-cortical regions was also predictive of better memory performance in temporal lobe epilepsy (McCormick et al 2014). In a study on autobiographical retrieval in healthy adults, we found enhanced connectivity between the postHC and posterior cortical regions when individuals were retrieving perceptual details of events as compared with generating memories from verbal cues (McCormick et al 2013b). Thus, we hypothesized that RIM performance in healthy adults would be positively correlated with the functional connectivity of postHC to the recollection memory network (Rugg and Vilberg 2013).…”
Section: Correlations Between Memory Performance and Resting State Fumentioning
confidence: 95%
“…Meta-analyses of imaging studies have shown that autobiographical memory tasks recruit similar vmPFC areas to self-trait processing along with a number of other brain areas including the hippocampus (Spreng, Mar, & Kim, 2009;Svoboda, McKinnon, & Levine, 2006). Furthermore, a recent study examined functional connectivity between the hippocampus and neocortex during the retrieval and elaboration of episodic memories and found that while the dmPFC is functionally coupled to the hippocampus during the retrieval of memories the vmPFC strongly coupled to it both during retrieval and when participants are required to relive the memory in elaborate detail (McCormick, St-Laurent, Ty, Valiante, & McAndrews, 2015). These results further demonstrate the importance of the vmPFC to the processing and experience of the conceptual self.…”
Section: Conceptual Selfmentioning
confidence: 99%